The Effect of Library Facility Modernization on the Educational Function at Universitas Negeri Padang Library - Indah Putri Rahmadini; Elva Rahmah (Darul Yasin Al Sys, 2026)
Although academic libraries have modernized their physical infrastructure and technological systems, the extent to which these improvements optimize their educational function in the digital era remains insufficiently examined. This study aims to analyze the influence of library facility modernization on the educational function of the library at Universitas Negeri Padang. A quantitative approach with a causal-associative design was employed. The study population comprised 8,282 library users in 2025, from which 99 respondents were selected through random sampling using the Slovin formula. Data were collected using a structured Likert-scale questionnaire that had been tested for validity and reliability, supported by literature review and documentation. The data were analyzed using descriptive and inferential statistics through simple linear regression with SPSS, following prerequisite tests of normality, linearity, and heteroscedasticity. The findings show that library facility modernization was categorized as good, with a mean score of 3.23, while the educational function of the library was also categorized as good, with a mean score of 3.24. Regression analysis revealed that facility modernization had a positive and significant effect on the educational function of the library, with a regression coefficient of 0.931 and a significance level below 0.05. The correlation coefficient of 0.842 indicates a very strong relationship, and the coefficient of determination of 0.708 shows that facility modernization explains 70.8% of the variance in the library’s educational function. The study concludes that improving library facility modernization significantly strengthens the educational function of academic libraries. These findings contribute to the development of user-oriented academic library services by emphasizing the importance of facility enhancement, digital accessibility, and information literacy support in promoting effective learning in higher education.